TRENDS IN ENSURING SPIRITUAL AND IDEOLOGICAL SECURITY IN THE CONTEXT OF GLOBALIZATION - Salaeva Laylo Shavkatovna (The Conference Hub, 2025)
This article presents a scientific analysis of the unique aspects of ensuring spiritual and ideological security in the era of globalization. It emphasizes that the rapid pace of globalization has intensified the emergence of ideological threats, which aim to influence and control human consciousness and moral values. The growing impact of foreign ideologies and concepts is explored as a challenge to national identity, cultural heritage, and social stability. The article also discusses the importance of strengthening ideological resilience in society and proposes strategic approaches to protecting spiritual and ideological integrity in the face of global challenges.
Keywords: ideology, globalization, security, world, individual, state, society, spirituality, information, propaganda, ideas.